Avoiding Revictimization: Shifting from Police Interrogations to Police Interviewing in China - Yuan, Chuanyou (International Journal of Speech, Language and the Law, 2010)
The present thesis conducts a forensic linguistic study on the issue of revictimization not of rape victims but of battered women suspects who go on to kill their aggressors (Walker 1999, Liu and Chan 1999, Zhao 2001, Tang etal. 2002).Awarding Institution: Guangdong University of Foreign StudiesDate of award: December 2007